2020
DOI: 10.1111/mmi.14590
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in enterobacterial common antigen biosynthesis restore outer membrane barrier function in Escherichia coli tol‐pal mutants

Abstract: Gram-negative bacteria are surrounded by a multilayered cell envelope consisting of the inner membrane (IM), the peptidoglycan layer, and the outer membrane (OM). This envelope structure, in particular the OM, plays an essential role in preventing toxic molecules from entering the cell, contributing to intrinsic resistance of Gram-negative bacteria against many antibiotics and detergents (Nikaido, 2003). The OM bilayer is asymmetric and has a unique lipid composition, comprising lipopolysaccharides (LPS) in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…Typhimurium, and S . Enteritidis (Gilbreath et al, 2012 ; Jaiswal et al, 2015 ; Jiang et al, 2020 ; Rai et al, 2021 ). ECA consists of trisaccharide repeating unit, GlcNAc, ManNAcA, and 4-acetamido-4,6-dideoxy-D-galactose (Fuc4NAc).…”
Section: Discussionmentioning
confidence: 99%
“…Typhimurium, and S . Enteritidis (Gilbreath et al, 2012 ; Jaiswal et al, 2015 ; Jiang et al, 2020 ; Rai et al, 2021 ). ECA consists of trisaccharide repeating unit, GlcNAc, ManNAcA, and 4-acetamido-4,6-dideoxy-D-galactose (Fuc4NAc).…”
Section: Discussionmentioning
confidence: 99%
“…Rcs is also activated by mutants of the Tol-Pal system which has a role in maintaining lipid homeostasis in the outer membrane ( Clavel et al, 1996 ; Shrivastava et al, 2017 ). It has been shown that Tol mutants show enhanced sensitivity to vancomycin, and this is rescued by mutants in the wec operon ( Jiang et al, 2020 ). Thus, the fact that both tolA and wec mutants show enhanced resistance to model honey could be directly related to the defect in ECA biosynthesis or to the induction of the Rcs phosphorelay, and this will repay further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments to determine the phospholipid distribution between IM and OM and the ratio of phospholipid to LPS at the OM were repeated exactly as described previously [127], with one addition, cell cultures were harvested at stationary phase (18 h growth) in addition to midexponential phase of growth (OD 600 = 0.5). Briefly, cultures were grown in triplicate in either 5 ml (stationary) or 10 ml LB (mid-exponential) with 1 μCi/ml [ 32 P]-disodiumphosphate (Perkin Elmer, NEX011001MC) to label phospholipids and LPS.…”
Section: Membrane Lipid Composition Analysesmentioning
confidence: 99%
“…Cells were harvested by centrifugation, washed, and resuspended in 5 ml of 20% sucrose in 10mM Tris-HCl (pH 8.0 (w/w) containing 1 mM PMSF and 50 μg/ml DNase I), and lysed using a high-pressure French press. The cell lysate was centrifuged and the supernatant subjected to sucrose density fractionation over 16 h, as described previously [127]. IM (7)(8)(9) and OM (12)(13)(14) fractions were collected and concentrated into 320 μl TBS and LPS and/or phospholipid extracted and dried as described previously [128].…”
Section: Membrane Lipid Composition Analysesmentioning
confidence: 99%